Sexually dimorphic therapeutic response in bortezomib-induced neuropathic pain reveals altered pain physiology in female rodents - Stockstill, Katherine (Pain, 2020)
Chemotherapy-induced neuropathic pain (CINP) in both sexes compromises many current chemotherapeutics and lacks a FDA-approved therapy. We recently identified the sphingosine-1-phosphate receptor subtype 1 (S1PR1) and A(3) adenosine receptor subtype (A(3)AR) as novel targets for therapeutic intervention. Our work in male rodents using paclitaxel, oxaliplatin and bortezomib showed robust inhibition of CINP with either S1PR1 antagonists or A(3)AR agonists. The S1PR1 functional antagonist FTY720 (Gilenya®) is FDA approved for treating multiple sclerosis and selective A(3)AR agonists are in advanced clinical trials for cancer and inflammatory disorders, underscoring the need for their expedited trials in CINP patients as chemotherapy adjuncts. Our findings reveal that S1PR1 antagonists and A(3)AR agonists mitigate paclitaxel and oxaliplatin CINP in female and male rodents, but failed to block or reverse bortezomib-induced neuropathic pain (BINP) in females. Although numerous mechanisms likely underlie these differences, we focused on receptor levels. We found that BINP in male rats, but not female rats, was associated with increased expression of A(3)AR in spinal cord dorsal horn, while S1PR1 levels were similar in both sexes. Thus, alternative mechanisms beyond receptor expression may account for sex differences in response to S1PR1 antagonists. Morphine and duloxetine, both clinical analgesics, reversed BINP in female mice, demonstrating that the lack of response is specific to S1PR1 and A(3)AR agents. Our findings suggest that A(3)AR- and S1PR1-based therapies are not viable approaches in preventing and treating BINP in females and should inform future clinical trials of these drugs as adjuncts to chemotherapy.